“Cost-benefit” analysis: defining the expediency of it application in CSR - Botsian, Tetiana; Diachek, Svitlana (Technology audit and production reserves, 2015)
This paper provides an introduction to the problem of usage and effectiveness of “cost-benefit” analysis in social responsible activity through worldwide case studies. The main purpose of the paper is to persuade that comparing costs and benefits of social activity change the essences of CSR (corporate social responsibility). We analyzed of case-studies of CSR performance to do it. The cases indicate that in the context of social responsibility the usage of financial valuators in relation to social objects as incentives as well as a “cost-benefit” analysis abolish the very concept of social responsibility. CSR have to be done taking in accounts specific inputs and output of social activity without using traditional economic utilitarian approach. In the case when the event is economically advantageous to be socially responsible it should have moral value. We states that this method of financial analysis in practice of CSR should abandon We propose during the analysis of any case in CSR proceed from the fact that it was adopted on the basis of "cost-benefit" analysis in a situation of "what if…?". This does not affect the calculation of effectiveness of CSR activity; however it will valuates the moral aspect of the issue.